Characterisation of the patients with suspected heart failure: experience from the SHEAF registry. Issue 1 (11th January 2021) - Garg, Pankaj; Dakshi, Ahmed; Assadi, Hosamadin; Swift, Andrew J; Naveed, Umna; Fent, Graham; Lewis, Nigel; Rogers, Dominic; Charalampopoulos, Athanasios; Al-Mohammad, Abdallah
Abstract : Objectives: To characterise and risk-stratify patients presenting to a heart failure (HF) clinic according to the National Institute for health and Care Excellence (NICE) algorithm. Methods: This is an observational study of prospectively collected data in the Sheffield HEArt Failure registry of consecutive patients with suspected HF between April 2012 and January 2020. Outcome was defined as all-cause mortality. Results: 6144 patients were enrolled: 71% had HF and 29% had no HF. Patients with N-terminal pro-brain-type natriuretic peptide (NT-proBNP) >2000 pg/mL were more likely to have HF than those with NT-proBNP of 400–2000 pg/mL (92% vs 64%, respectively). Frequency of HF phenotypes include: HF with preserved ejection fraction (HFpEF) (33%), HF with reduced ejection fraction (HFrEF) (29%), HF due to valvular heart disease (4%), HF due to pulmonary hypertension (5%) and HF due to right ventricular systolic dysfunction (1%). There were 1485 (24%) deaths over a maximum follow-up of 6 years. The death rate was higher in HF versus no HF (11.49 vs 7.29 per 100 patient-years follow-up, p<0.0001). Patients with HF and an NT-proBNP >2000 pg/mL had lower survival than those with NT-proBNP 400–2000 pg/mL (3.8 years vs 5 years, p<0.0001). Propensity matched survival curves were comparable between HFpEF and HFrEF (p=0.88). Conclusion: Our findings support the use by NICE's HF diagnostic algorithm of tiered triage of patients with suspected HF based on their NT-proBNP levels. The two pathways yielded distinctive groups of patients with varied diagnoses and prognosis. HFpEF is the most frequent diagnosis, with its challenges of poor prognosis and paucity of therapeutic options.